GPVI down-regulation in murine platelets through metalloproteinase-dependent shedding - Bergmeier, Wolfgang; Rabie, Tamer; Strehl, Amrei; Piffath, Crystal L.; Prostredna, Miroslava; Wagner, Denisa D.; Nieswandt, Bernhard (Thrombosis and Haemostasis, 2004)
Platelet interaction with subendothelial collagen is crucial for hemostasis and thrombosis. Under conditions of elevated shear, platelet adhesion and activation on collagen requires the coordinated action of glycoprotein (GP) Ib and GPVI, which may be physically and functionally linked in the platelet membrane. While the surface expression of GPIb can be down-regulated by internalization and/or proteolytic cleavage of a 130 kDa fragment of GPIbα (glycocalicin, GC), very little is known about the cellular regulation of GPVI. We have recently shown that GPIb on platelets is cleaved by metalloproteinase-dependent mechanisms in response to mitochondrial injury. In the current study, we examined a possible role of platelet metalloproteinases in the regulation of GPVI. Mitochondrial injury induced by incubation of mouse platelets with carbonyl cyanide m-chlorophenyl-hydrazone (CCCP) severely affected the cells´ responses to collagen or the GPVI-specific agonist, collagen related peptide (CRP), but not to thrombin or the stable thromboxane A2 analog U46619.This defect was due to a rapid proteolytic cleavage of GPVI, as shown by the release of the 55 kDa extracellular domain into the supernatant. Both the proteolysis of GPVI and the loss of its activity were inhibited in the presence of the broad range metalloproteinase inhibitor, GM6001. Platelet stimulation with thrombin or CRP, however, resulted in marked metalloproteinase-dependent shedding of GPIbα, but not GPVI suggesting that different metalloproteinases are involved in the regulation of the two receptors or, alternatively, an additional signal is required to render GPVI susceptible to cleavage.
Keywords: Collagen; glycoprotein; metalloproteinase; platelet; shedding